Using cryo‐electron microscopy maps for X‐ray structure determination of homologues. Issue 1 (2nd January 2020) - Zeng, Lingxiao; Ding, Wei; Hao, Quan
Abstract : A hybrid method has been developed to determine crystal structures by utilizing cryo‐EM maps of homologous proteins. Abstract : The combination of cryo‐electron microscopy (cryo‐EM) and X‐ray crystallography reflects an important trend in structural biology. In a previously published study, a hybrid method for the determination of X‐ray structures using initial phases provided by the corresponding parts of cryo‐EM maps was presented. However, if the target structure of X‐ray crystallography is not identical but homologous to the corresponding molecular model of the cryo‐EM map, then the decrease in the accuracy of the starting phases makes the whole process more difficult. Here, a modified hybrid method is presented to handle such cases. The whole process includes three steps: cryo‐EM map replacement, phase extension by NCS averaging and dual‐space iterative model building. When the resolution gap between the cryo‐EM and X‐ray crystallographic data is large and the sequence identity is low, an intermediate stage of model building is necessary. Six test cases have been studied with sequence identity between the corresponding molecules in the cryo‐EM and X‐ray structures ranging from 34 to 52% and with sequence similarity ranging from 86 to 91%. This hybrid method consistently produced models with reasonable R work and R free values which agree well with the previously determined X‐ray structures for all test cases, thus indicating the general applicability of the method for X‐ray structure determination of homologues using cryo‐EM maps as a starting point.